Soil bacterial community characteristics and influencing factors in different types of farmland shelterbelts in the Alaer reclamation area - Tian, Cuiping; Wu, Xue; Bahethan, Bota; Yang, Xianyao; Yang, Qianqian; Wang, Xiantao (Frontiers in Plant Science, 2024)
To investigate the effects of various types of farmland shelterbelts on soil quality and soil bacterial community diversity, this study focused on soil samples from four different shelterbelt types in the Alaer reclamation area, including Populus euphratica Oliv.- Populus tomentosa Carrière (PP), Elaeagnus angustifolia L.- Populus euphratica Oliv. (EP), Populus alba var. pyramidalis Bunge (P), and Salix babylonica L. (S). We analyzed their physical, chemical, biological properties as well as the differences in bacterial community structure, and explored the influencing factors on soil microbial community characteristics through microbial correlation network analysis. The results showed that: (1) There were significant differences in soil properties among the four types of farmland shelterbelts (p < 0.05), with P soils exhibiting the highest levels of organic matter, total nitrogen, and total phosphorus contents. (2) The Alpha diversity indices of soil bacteria showed significant differences among the four types of farmland shelterbelts (p < 0.05), with the P soils displayed the highest Chao1 and Shannon indices. (3) There were differences in the composition and abundance of dominant soil bacterial communities among different farmland shelterbelts, notably, the abundances of Verrucomicrobia, Acidobacteria, and Planctomycetes were significantly higher in P soils compared to the other three types. (4) The complexity of the correlation network between microbial species and environmental factors was highest in EP soils, soil microbial biomass nitrogen and available phosphorus were the main influencing factors. These findings indicated that different types of farmland shelterbelts had significant impacts on soil properties and soil bacterial communities. Soil bacterial communities were regulated by soil properties, their changes reflected a combined effect of soil characteristics and tree species.